Health system adaptation to extreme weather events in Australia: A scoping review - Rupert Legg; Jason Prior; Erica McIntyre; Edgar Liu; Mikaela Tracy; Leona Tan; Angela Dawson; John Richmond; Clare Perry (The Journal of Climate Change and Health)
Introduction: The increasing prevalence and severity of extreme weather events is likely to present challenges for the systems in which humans operate. This review investigates how the health system in Australia, a region heavily affected by bushfires, floods, droughts and extreme heat, is adapting to the risks presented by extreme weather events and how these adaptations are being evaluated. Methods: By searching Medline, PsycINFO, Scopus and Web of Science for peer reviewed literature reporting on health system adaptations, 33 articles published between 2014 and 2023 were identified for inclusion. Results: Primarily, articles documented adaptations that, consistent with the World Health Organization's health system building blocks, focused on: the health workforce; health information systems; leadership and governance; and service delivery. Little attention was placed on access to essential medicines and health system financing. It was also most common for adaptations to address flooding, extreme heat, bushfires, and storms, reflecting the impact of such events in Australia. Adaptations tended to result in beneficial outcomes, including improved workforce capability, better health outcomes, reduced demand on and risk of overburdening the health system, lowered costs, and greater financial stability. However, how these elements come together to build health system resilience is unclear and barriers remain that reduce the effectiveness of adaptations. Conclusion: To ensure that Australia's health system is resilient to extreme weather events, future adaptations should focus particularly on access to essential medicines and financing, while future research should evaluate the outcomes of adaptations in a consolidated and systematic way.